Morbidity from antiretroviral metabolic effects in Africa: The Mama Study - Karamchand, Sumanth (Division of Clinical Pharmacology, 2018)
Introduction: Combination antiretroviral therapy (ART) has considerably reduced both the morbidity and mortality of Human Immunodeficiency Virus (HIV) infection and its associated complications, thus effectively transforming a fatal disease into a manageable chronic condition. However, the chronic use of ART has been accompanied by the emergence of adverse metabolic abnormalities in HIV-infected patients, including dysglycaemia. There is, however, a paucity of data from sub-Saharan Africa on the incidence and risk factors associated with new onset diabetes mellitus in the HIV-infected population. Furthermore, efavirenz is the preferred nonnucleoside reverse transcriptase inhibitor (NNRTI) in first-line antiretroviral therapy (ART) regimens in low- and middle-income countries, where the prevalence of diabetes is increasing. Randomized control trials have shown mild increases in plasma glucose in participants in the efavirenz arms, but no association has been reported with overt diabetes. This study explores the risk factors and incidence of diabetes, and in particular the association between efavirenz exposure and diabetes, in a large Southern African cohort commencing NNRTI-based first-line ART. Subjects and Methods: The study cohort included HIV-infected adults commencing NNRTI-based ART in a private sector HIV disease management programme from January 2002 to December 2011. Incident diabetes was identified by the initiation of diabetes treatment. Patients with prevalent diabetes were excluded. The incidence of diabetes in patients receiving efavirenz versus nevirapine containing regimens was compared with a Kaplan-Meier plot and a log-rank test. The association of efavirenz exposure with the hazard of developing diabetes was modelled using a multivariate Cox-proportional hazards model. The following variables were adjusted for in the regression model: age, sex, baseline BMI, baseline CD4, baseline viral load, exposure to diabetogenic drugs, and nucleoside reverse transcriptase inhibitor (NRTI) exposure. Results: Between January 2002 and June 2011, 62,467 patients commenced ART in the AfA program, of whom 56,298 patients met the inclusion and exclusion criteria and were included in the analysis. Median follow-up was 1.56 years (interquartile range (IQR): 0.71- 2.79 years), 21.7% of patients were followed up for 3 or more years. New onset diabetes was identified in 1500 (2.66%) patients over 113,297 patient-years of follow-up (PYFU), giving a crude incidence of 13.24 cases per 1000 PYFU. In the multivariate analysis treatment with efavirenz rather than nevirapine was associated with increased risk of developing diabetes (hazard ratio 1.27 (95% confidence interval: 1.10 - 1.46). Zidovudine and stavudine exposure, older baseline age, elevated baseline BMI, and exposure to diabetogenic medication were also associated with increased risk of diabetes. No association was found between baseline CD4 and an increased risk of diabetes. There was an association between the lowest stratum of baseline viral load and an increased relative risk for developing diabetes, but no association with higher viral load strata. Conclusion: Treatment with efavirenz, as well as stavudine and zidovudine, increased the risk of incident diabetes. Interventions to detect and prevent diabetes should be implemented in ART programmes, and use of antiretrovirals with lower risk of metabolic complications should be encouraged.